ANALYSIS OF THE URBAN HEAT ISLAND PHENOMENON IN WEST KALIMANTAN PROVINCE USING GOOGLE EARTH ENGINE - Fahrulaji; Muhammad Pramulya; Hendra Perdana (Malaysian Journal of Tropical Geography (MJTG), 2025)
Urban Heat Islands (UHI) refer to areas where urban temperatures are significantly higher than those in surrounding rural regions. This study utilizes remote sensing data from Google Earth Engine to examine spatiotemporal UHI variations in West Kalimantan Province from 2019 to 2023 by analyzing land surface temperature (LST) and vegetation density. The findings reveal that urban areas, especially Pontianak, experienced higher UHI intensity, with temperature differences ranging from 0.5°C to 2°C compared to more vegetated rural zones. Interior regions with dense vegetation showed lower UHI effects, whereas coastal cities such as Pontianak, Kubu Raya, and Mempawah exhibited UTFVI values above 0.02, indicating moderate to strong clustering of UHI. During the COVID-19 pandemic (2020–2021), average temperatures decreased by approximately 2°C due to reduced anthropogenic activity, but rebounded in 2022–2023. The province was categorized into four UHI intensity levels: strong (4 regions), moderate (3), weak (2), and non-UHI (5). These results highlight the crucial role of vegetation in mitigating UHI and emphasize the need for sustainable spatial planning that incorporates green infrastructure to enhance urban thermal comfort and resilience.